Voices of social education : a pedagogy of change - Pohl, Bernardo E., 1969-; White, Cameron; Beaudry, Christine (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"There is only one place where social education can occur and flourish: through the voices that create a pedagogy of change. And it is these voices where the most exciting and provocative moments can occur for those of us who are passionate about education, teaching, social justice, equity, and love. As such, social education is a journey-an endeavor that makes us savor the experience of the journey more than the destination. And social education is a journey that ins enhanced through educator and student voices because it occurs in the most important spaces of our personal and professional lives. It occurs in the hallways of the schools we teach, in the staff meetings we attend, in the mountain villages we venture to visit, in the places we work, and in the spaces we occupy. Moreover, social education is a unique kind of journey because it is a human experience that seldom occurs alone. It happens with our colleagues and our loved ones. It happens with our students, administrators, and other professionals who are fighting for the same things that we so fervently believe. In the end, social education occurs and flourishes in the trenches because it is the active pursuit of getting our hands dirty in our endless pursuit for a better and more just world. Social education is also a narrative, which takes on a different meaning for each one of us. This is because sooner or later each person that embarks into the journey of social education develops its own personal definition of what social education entails through his or her own personal landscape and knowledge. This personal landscape has been evolving since we were very young with some of the best examples of human courage and tenacity in the fight for social justice. Social Education Voices: A Pedagogy for Change is a collection of personal stories. In this volume, academics, teachers, students, activists, and artists share their personal stories of triumph, tribulations, and courage in their daily fight for social justice and equality. The term social education is not defined as a set number of guidelines or a specific definition; we give the term an organic fluency to stress that social education is a point of encounter--a common space-- where we can share with each other our experiences, values, and culture to form a more genuine and just social experience"--